2009
DOI: 10.1007/s10895-009-0498-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Morphological Properties of Divinylbenzoxazolylbiphenyl Thin Films

Abstract: The thin organic films based on 4,4'-bis-[(Z)-1-(1,3-benzoxazol-2-yl-2-ethenyl)]biphenyl and its partly fluorinated derivatives are studied. Absorption, luminescence, and excitation spectra, luminescence decay and film morphology were found to depend sensitively on the changes in molecule structure, nature and temperature of the substrate, as well as the thermovacuum deposition rate, being the origins of bad reproducibility of the optical properties of such films. Molecular aggregation with chromophore dipoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…α-and β-phases have two mer-Alq 3 molecules in a unit cell, while δ-phase has four fac-Alq 3 per unit cell [23]. Also, the morphology of vacuum deposited organic lms depends strongly on the substrate [32]. Zinc oxide nanostructure was employed as catalyst in organic syntheses and transformations [33].…”
Section: Resultsmentioning
confidence: 99%
“…α-and β-phases have two mer-Alq 3 molecules in a unit cell, while δ-phase has four fac-Alq 3 per unit cell [23]. Also, the morphology of vacuum deposited organic lms depends strongly on the substrate [32]. Zinc oxide nanostructure was employed as catalyst in organic syntheses and transformations [33].…”
Section: Resultsmentioning
confidence: 99%
“…The observed difference in electric field behavior of these molecules can be explained by the difference in the dipole moment. More specific techniques like positron annihilation spectroscopy may be needed to analyze the details [ 21 , 22 ], but it can be noticed that the morphology of vacuum deposited organic films depends strongly on the type of substrate and its temperature [ 23 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In varying solvent or temperature, different aggregation morphologies could be prepared, resulting in wide differences in luminescent properties. 16,17 As to the molecular structure modifying, the introduction of long-chained alkoxy could increase the solubility and rheological properties of conjugated molecule, and then improve the film-forming capability, leading to optimized spin-coated film morphology. 18 Usually, as for one material, a more aggravated aggregation state led to red-shifted and broader absorption spectra.…”
Section: Introductionmentioning
confidence: 99%
“…In the solid or aggregation state, the conjugated aromatic hydrocarbon tends to form excimer and/or exciplex due to the intermolecular interaction including π–π stacking, electrostatic attractions and van der Waals force, which, in most time, results in a drastic decrease of their luminescence efficiency. , Studies on the aggregation state of organic luminescence materials revealed that the aggregation morphology was dominated by molecular structure of the materials, , temperature, solvent, and other kinetic parameters. In varying solvent or temperature, different aggregation morphologies could be prepared, resulting in wide differences in luminescent properties. , As to the molecular structure modifying, the introduction of long-chained alkoxy could increase the solubility and rheological properties of conjugated molecule, and then improve the film-forming capability, leading to optimized spin-coated film morphology . Usually, as for one material, a more aggravated aggregation state led to red-shifted and broader absorption spectra …”
Section: Introductionmentioning
confidence: 99%